La navigazione impossibile. Lettura di Seneca, De otio 8 - Berno, Francesca Romana (Lucius Annaeus Seneca, 2024)
This paper offers a close reading of Seneca’s De otio 8, providing some evidence for the theory according to which it would represent the ending of the dialogue: it summons and deepens several motifs hinted at in the previous chapters; it alludes to the opening of Cicero’s De re publica; it deals with the shipwreck metaphor, a seminal image in Seneca’s prose works. Furthermore, the quoted historical examples – Socrates, Aristoteles and Hannibal, unjustly prosecuted by their own fellow citizens – may suggest a political reading of the passage, in the light of a self-defence.